A Study of Accelerated Aging and Seed Storage on the Germination of Anaphalis longifolia (Blume) Blume ex.DC. - Muhammad Imam Surya; Suluh Normasiwi (Jurnal Ilmu Kehutanan)
Anaphalis longifolia is a group of edelweiss flowers which has a highly conservation value. However, there are only limited information on conservation activities of A. longifolia regarded to the seed storage and cultivation. The study was conducted in the laboratory of Cibodas Botanical Garden. In this study, two experiments were carried out. In the first experiment, A. longifolia seeds were treated by ethanol 96% with 11 different immersion time (0, 10, 20, 30, 40, 50, 60, 70, 80, 90 and 100 minutes). In the second experiment, seed storability and viability test were conducted after A. longifolia seeds were saved in desiccator, cabinet, refrigerator 4 oC and freezer -20 oC during 12 months. Results of the first experiment showed that soaking seeds on 96% ethanol for 10-30 minutes was able to stimulate seed germination of A. longifolia. Freezer with temperature -20 oC is recommended to storage A. longifolia for long periods.